Transfusion independence after lenalidomide discontinuation in patients with del(5q) myelodysplastic neoplasm: a HARMONY Alliance study - Crisà, Elena; Mora, Elvira; Germing, Ulrich; Bally, Cecile; Diez Campelo, Maria; Myllymäki, Mikko; Jädersten, Martin; Komrokji, Rami; Platzbecker, Uwe; Haase, Detlef; Hofmann, Wolf-Karsten; Al Ali, Najla H.; et al. (Leukemia, 2024)
Lenalidomide (LEN) can induce red blood cell-transfusion independence (RBC-TI) in 60-70% of del(5q) myelodysplastic neoplasm (MDS) patients. Current recommendation is to continue LEN in responding patients until failure or progression, with likelihood of toxicity and a high cost for healthcare systems. This HARMONY Alliance study investigated the outcome of MDS del(5q) patients who discontinued LEN while RBC-transfusion independent. We enrolled 118 patients with IPSS-R low-intermediate risk. Seventy patients (59%) discontinued LEN for intolerance, 38 (32%) per their physician decision, nine (8%) per their own decision and one (1%) for unknown reasons. After a median follow-up of 49 months from discontinuation, 50/118 patients lost RBC-TI and 22/30 who underwent cytogenetic re-evaluation lost complete cytogenetic response. The median RBC-TI duration was 56 months. In multivariate analysis, RBC-TI duration after LEN discontinuation correlated with low transfusion burden before LEN therapy, treatment ≥ 12 LEN cycles, younger age and higher Hb level at LEN withdrawal. Forty-eight patients were re-treated with LEN for loss of response and 28 achieved again RBC-TI. These data show that stopping LEN therapy in MDS del(5q) patients who reached RBC-TI allows prolonged maintenance of TI in a large subset of patients.